The effect of using the strategy Learning by playing for some skills handball patting According to the curriculum for female students Second stage, College of Physical Education and Sports Sciences, University of Baghdad - Hussein, Yasir (Journal of Physical Education, 2025)
The aim of the research was to identify  On the effect of the learning-by-play strategy on learning some handball skills among second-stage female students,Comparing the results of students' performance before and after implementing the learning by playing strategy,Providing development proposals for teaching handball skills in light of the research results.,I dependresearcherCurriculumexperimentalIn research procedures as an appropriate approach to achieving research objectives,For two groups, one experimental and the other control,Community of female studentsSecondFor the academic year 2024-2025, consisting of (4Female people (numbering)151) StudentChosen.Research sample30 female students from Section (B) were selected and (4) female students were excluded for the exploratory experiment. The researcher divided the sample, which numbered (26) female students, into two groups randomly: an experimental group in which the (learning by playing method) was used, and a control group (in which the extended curriculum was used). Conclusions Interactive activities and games accompanying the educational units contributed to developing and enhancing understanding and practical application of the skill. Educational units prepared and designed according to the play method proved to be effective in achieving the cognitive and skill objectives of the subject. The play-based learning method enhanced students' motivation towards good learning, and raised the level of participation and interaction within the educational unit. Recommendations: - Involve students in evaluating educational activities. Adopt the play-based learning method in teaching basic skills for all sports. Encourage teachers to design educational units that integrate play-based learning in the early stages of education. Conduct more research on other handball skills and other activities. Conduct more modern strategies for learning sports skills and compare them with traditional ones.